Pelaksanaan Program Gerakan Literasi Sekolah (GLS) dalam Menumbuhkan Minat Baca Peserta Didik - Euis Heriyanti; Tatu Hilaliyah; Rina Yuliana (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This research is based on the government's efforts to foster reading interest with the establishment of the School Literacy Movement (GLS) program. the school literacy movement program (GLS) in fostering students' reading interest, to describe the impact of implementing the school literacy movement program (GLS) on students' reading interest. The approaches and methods used are qualitative approaches and descriptive methods through data collection techniques such as triangulation techniques such as interviews, observations, and documentation using the Miles and Huberman data analysis models consisting of the process of data collection, data reduction, data presentation, and verification/drawing conclusions. The results of the research show that the implementation of the literacy movement program was successful, this was proven through the results of interviews related to supporting and inhibiting factors for the school literacy movement that in the school there are supporting roles such as facilities and infrastructure while the inhibiting role is only technical implementation, in the related observation process the teacher's efforts in the literacy movement program where the teacher has been quite good at implementing GLS in fostering students' interest in reading.